CHARACTERIZATION OF FLAVONOID COMPOUNDS - Ridwanuloh, Dadan; Syarif, Fadilah; Sukma, Andhi (International Journal of Psychosocial Rehabilitation, 2020)
The use of plants in Indonesia is widely used as herbal medicines in an effort to maintain public health. One type of plants used as herbal medicines is the Ciplukan plant, Physalis angulata L. The activity of the P.angulata L. plant is as antihyperglycemic, antibacterial, antiviral, immunostimulant and immunosuppressant (immunomodulatory), anti-inflammatory, antioxidant, and cytotoxic properties. One of the secondary metabolite compounds which has this activity is the Flavonoid group. Therefore, the purpose of this study was to identify the flavonoid compounds contained in the Ciplukan plant, P.angulata L. The methods used were Phytochomia Test, Thin Layer Chromatography, Column Chromatography, and UV-Vis Spectrophotometry. Phytochemical test results show that the Ciplukan stem contains quinone, flavonoid, saponin, and monosesquiterpeoid compounds, and polyphenols. TLC test with n-hexane-ethyl acetate (7: 3) eluent showed a blue chromatogram with Rf 0.8 cm. Several fractions of the results of the chromatography column later in UV-Vis Spectrophotometry showed the compound was a flavonoid type of flavanone.